Preferences for childbirth delivery and pain relief methods among pregnant women in Vietnam - Nguyen, Tham Thi; Nguyen, Long Hoang; Nguyen, Ha Thu Thi; Dam, Vu Anh Trong; Vu, Thuc Minh Thi; Latkin, Carl A.; Zhang, Melvyn W. B.; Ho, Roger C. M.; Ho, Cyrus S. H. (Frontiers in Medicine, 2024)
Background: Understanding childbirth delivery and pain relief method preferences is important as a part of the shared decision-making process between pregnant women and health professionals. This study aimed to examine the preferences for childbirth delivery modes and pain relief methods and factors related to these preferences among pregnant women in Vietnam. Methods: A cross-sectional survey on pregnant women was conducted in two obstetrics hospitals in Vietnam. Face-to-face interviews using a structured questionnaire were performed to collect information about sociodemographic characteristics, pregnancy characteristics, preferences for different childbirth delivery modes, and pain relief methods. Multivariate logistic regression was employed for determining associated factors with the preferences. Results: Of 576 pregnant women, 34% of participants preferred cesarean section. Most of the sample did not have any preferences for specific pharmacological pain relief methods (70.1%), while support from partner/relatives was the most preferable non-pharmacological method (61.3%), following by water birth (11.1%) and acupuncture (9.9%). Desire to have another baby, relatives’ experience, selection date of birth, and instrumental social support were major drivers of the cesarean section selection. This preference was an important factor in the preference for pharmacological pain relief. Meanwhile, high levels of informational and emotional support were associated with non-pharmacological method preference. Conclusion: This study highlighted a high preference rate for cesarean section in urban pregnant women in Vietnam. Holistic approaches from family, health facility, and policy should be performed to diminish the cesarean rate preference and promote the use of non-pharmacological pain relief methods during birth.